Tinjauan Yuridis Tentang Prosedur Penerbitan Sertifikat Atas Tanah Di Desa Waemulang Kabupaten Buru Selatan Berdasarkan Program Pemerintah - Solissa, Fandri; Laturette, Adonia Ivone; Uktelseja, Novyta (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Based on the reality that occurs in everyday life in the environment where the author lives, namely in the village of Waemulang, Leksula sub-district, South Buru Regency, where the community The problems that occur in the Waemulang village community in South Buru district are related to the cancellation of land rights certificates that occur in today's society. This, started with the existence of a government program regarding the National Agrarian Project Operation (PRONA) for making certificates of land rights.Purposes of the Research: This writing aims to find out the procedures for obtaining certificates of land rights based on government programs, to find out what are the grounds for objections to the issuance of land title certificates issued by the national land agency, and as one of the academic requirements in completing studies at the Faculty of Law, University of PattimuraMethods of the Research: The normative juridical research method is descriptive analysis in nature, namely obtaining data from the library in the form of documents, books, magazines and other literature related to writing. The source of legal material used is Primary legal material, Secondary legal material, and Tertiary legal material and used as a technique for collecting legal material, then processing and analyzing legal material through qualitative analysis, namely the data obtained is then systematically arranged for further qualitative analysis based on scientific disciplines. Civil law to achieve clarity of issues to be discussed.Results of the Research: The results of the study show that the procedure for issuing land certificates in obtaining land rights is carried out by the land registration process, so that there is a guarantee of legal certainty for all right-holders, while the procedure for obtaining land rights, namely the procedure for land registration is carried out sporadically at the request of interested parties, and procedures Systematic land registration is carried out according to work plans carried out in designated areas. A conflict can lead to disputes so that dispute resolution can be done in several ways: Dispute resolution through formal courts, through administrative efforts and through lawsuits.